Laboratory Monitoring in Emicizumab-Treated Persons with Hemophilia A - Müller, Jens; Pekrul, Isabell; Pötzsch, Bernd; Berning, Beate; Oldenburg, Johannes; Spannagl, Michael (Thrombosis and Haemostasis, 2019)
Hemophilia A (HA) is an X-linked hereditary bleeding disorder caused by deficiency of coagulation factor (F) VIII activity. One of the greatest complications in the treatment of HA is the development of neutralizing alloantibodies, known as FVIII inhibitors. HA patients who develop FVIII inhibitors have limited treatment options available to them and experience greater disease- and treatment-related burdens than HA patients without FVIII inhibitors. Emicizumab, a recently approved bispecific monoclonal antibody, mimics the function of FVIIIa by bridging FIXa and FX to restore effective hemostasis. Although emicizumab and FVIII show some functional similarities, several key differences influence the results of standard laboratory assays when conducted in the presence of emicizumab, and can result in a misleading interpretation of coagulation assays in emicizumab-treated patients. Here, we discuss current laboratory monitoring methods, including activated partial thromboplastin time, FVIII one-stage clotting assays, FVIII chromogenic assays, and global coagulations assays; address why these conventional methods may be inappropriate for monitoring of HA patients receiving emicizumab; and suggest alternative methods applicable to monitoring HA treatment in an evolving treatment landscape.
Keywords: hemophilia A; laboratory monitoring; FVIII activity; coagulation